Does acculturation narrow the health literacy gap between immigrants and non-immigrants—An explorative study. Issue 4 (April 2017) - Mantwill, Sarah; Schulz, Peter J.
Highlights: Immigrants in Switzerland have lower functional health literacy. Differences exist between language-dependent and independent health literacy. Length of stay in country is associated with language-dependent health literacy. Language-dependent health literacy is associated with health status. Abstract: Objectives: To compare functional health literacy (HL) levels in three immigrant groups to those of the German- and Italian-speaking non-immigrant population in Switzerland. Moreover, to investigate whether language-independent, respectively language-dependent, functional HL and variables of acculturation were associated with self-reported health status among immigrants. Methods: Language-independent HL was assessed with the Short Test of Functional Health Literacy (S-TOFHLA) in the respective native languages. Language-dependent HL was measured using Brief Health Literacy Screeners (BHLS) asking about participants' confidence in understanding medical information in the language of the host country. Measures of acculturation included length of stay and age when taking residency in Switzerland. Results: In particular Albanian- and Portuguese-speaking immigrants had lower levels of functional HL. In unadjusted analysis "age when taking residency in Switzerland" was associated with the BHLS. Adjusted analysis showed that the BHLS were significantly associated with self-reported health among all immigrant groups ( p ≤ 0.01). Conclusions: Functional HL that is dependent on understanding of medical information in the language of the new host country is a better predictor for self-reported health status among immigrants than language-independent HL. Practice implications: In the clinical setting limited functional HL might be a significant obstacle to successful disease treatment and prevention in immigrants.